Modelling of the Non-linear Biotransformation Process - T. Iswarya; L. Rajendran; KE. Sathappan (International Journal of Mathematics And its Applications, 2018)
Mathematical modelling of production of l-malic acid from fumaric acid which is performed by the action of the fumarase isolated from porcine heart and the fumarase in permeabilized baker's yeast cells are discussed. This model is based on nonlinear system of equations containing a non-linear term related to rate of the reactions. The effects of various parameters on the concentrations are also discussed. Our analytical results are also compared with numerical results (Sci lab program) and satisfactory agreement is noted. Simple analytical expressions for the concentration of substrate and product have been derived for all values of reaction parameters using the new homotopy perturbation method (NHPM). Kinetic parameters are also obtained from the enzyme reaction rate.